Young Adulthood Is the Crucible of Personality Development. (October 2016) - Roberts, Brent W.; Davis, Jordan P.
The last two decades have seen a rapid acceleration of research on personality development focusing on the periods of late adolescence and young adulthood. The findings paint a picture of surprising quiescence in adolescence followed by a period of tremendous growth and change in personality traits in young adulthood. The patterns and potential reasons for these changes are discussed in the context of the Neo-Socioanalytic model of personality and the theory of emerging adulthood. The potential for convergence and collaboration between the fields of personality development and emerging adulthood is discussed.